Stereoselective synthesis and properties of 1, 3-bis(dicyanomethylidene)indane-5-carboxylic acid acceptor fragment containing nonlinear optical chromophores. Issue 22 (5th May 2016) - Traskovskis, Kaspars; Kokars, Valdis; Tokmakovs, Andrejs; Mihailovs, Igors; Nitiss, Edgars; Petrova, Marina; Belyakov, Sergey; Rutkis, Martins
Abstract : A new indane based electron acceptor fragment has been developed and can be used to acquire NLO active chromophores with controlled stereochemistry. Abstract : A series of organic push–pull type chromophores using indane-1, 3-dione 5-carboxylic acid (IDCA) and novel 1, 3-bis(dicyanomethylidene)indane 5-carboxylic acid (CICA) electron acceptor fragments have been synthesized and characterized. NMR and X-ray analysis revealed that condensation reactions with the CICA fragment were stereoselective and yielded benzylidenes and azomethines with E double bond configurations. Due to the non-planar geometry these compounds are chiral and were acquired as a racemic mixture. The subsequent functionalization of the carboxylic acid group with 5, 5, 5-triphenylpentan-1-ol yielded solution-processable glass forming materials (6, 8, 10, 13 ) with glass transition temperature values of 76–134 °C. The nonlinear optical (NLO) properties of these compounds were characterized using quantum chemical calculations and second harmonic generation (SHG) measurements in corona-poled thin glassy films. The twisted geometry of the CICA based materials was shown to be beneficial to the macroscopic NLO performance due to the less pronounced solid phase stacking compared to the flat IDCA based compounds. The presence of site isolating groups at both the acceptor and donor ends of the molecule in compound13 resulted in a considerable NLO efficiency increase. Non-centrosymmetric crystals of CICA based N, N -dimethylaminobenzylidene7b were obtained and showed a SHG response comparable to urea.